2001
DOI: 10.1094/mpmi.2001.14.11.1335
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genomic Locus with Atypical G+C Content that Is Required for Extracellular Polysaccharide Production and Virulence in Xanthomonas oryzae pv. oryzae

Abstract: Three exopolysaccharide (EPS)- and virulence-deficient mutants of Xanthomonas oryzae pv. oryzae, the causal agent of bacterial leaf blight of rice, were isolated by Tn5 mutagenesis. These insertions are not located within the gum gene cluster. A 40-kb cosmid clone that restored EPS production and virulence to all three mutants was isolated, and the three transposon insertions were localized to contiguous 4.3- and 3.5-kb EcoRI fragments that are included in this clone. Sequence data indicate that two of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Scupham & Triplett (1997) reported that in Brucella abortus, mutation of galE (or exoB), which is involved in LPS and EPS production, does not cause visible changes in cell morphology. Dharmapuri et al (2001) found that Xanthomonas oryzae pv. oryzae mutants that are deficient in EPS and LPS production do not differ from the wildtype in colony roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Scupham & Triplett (1997) reported that in Brucella abortus, mutation of galE (or exoB), which is involved in LPS and EPS production, does not cause visible changes in cell morphology. Dharmapuri et al (2001) found that Xanthomonas oryzae pv. oryzae mutants that are deficient in EPS and LPS production do not differ from the wildtype in colony roughness.…”
Section: Discussionmentioning
confidence: 99%
“…The LPS locus in Xanthomonas is a hypervariable region which has a role in virulence (37). In Xanthomonas, the LPS cluster is confined between two highly conserved housekeeping genes, metB and etfA, encoding the cystathionine gamma lyase and electron transport flavoprotein, respectively (38).…”
Section: Sequencing and Assemblymentioning
confidence: 99%
“…Some of the functions encoded within these variable regions are also known to have an unusual base composition in other species or are known to vary among strains. These include the exopolysaccharide biosynthesis regions (11,14,17) and the restriction modification systems (38). Some variable regions have a base composition that is similar to the genome average.…”
Section: Fig 2 Conservation and Variability Of Genes In L Plantarumentioning
confidence: 99%